A CFD analysis on the effect of vortex finder and cylindrical length on cyclone hydrodynamics and centrifugal forces - Luqman Chuah, Abdullah; Jolius, Gimbun; Thomas, S. Y. Choong; A., Fakhru'l Razi (The Institution of Engineers Malaysia, 2008)
The article presents a Computational Fluid Dynamics (CFD) calculation to predict and to evaluate the flow field and centrifugal forces of gas cyclones. The numerical solutions were carried out using commercial CFD code FLUENT 6.0. The problem of modelling highly swirling flow is overcame by means of an algebraic turbulence model, and all the features of the experimentally observed gas flow in a cyclone are shown to be computationally reproduced. It was found that CFD simulations predict excellently the axial and tangential velocity with an average deviation of ± 0.5 m/s from the presented experimental data. The physical mechanism for prolonged cyclone cylindrical body and vortex finder has also been successfully elucidated. Specifically, results obtained from the computer modelling exercise have demonstrated that CFD with RSM turbulence model is suitable for modelling a flow field and hydrodynamic of cyclone.